The EXOSAT data on GX 339-4: further evidence for an "intermediate" state - Méndez, Mariano R. (1997)
We have studied the fast timing and spectral behavior of the black hole candidate (BHC) GX 339-4 using all 1 - 20 keV EXOSAT ME data: the July 1983, March 1984, May 1984 and April 1985 observations. In April 1985 GX 339-4 was in a weak low state (0.03E-9 erg cm^{-2} s^{-1}, 2 - 10 keV). The X-ray spectrum was a hard power law with a photon index α of 1.82 and the power spectrum, though ill-constrained by the data, was consistent with a typical BHC low state spectrum. During the other three pointings the system was brighter (1.5E-9 erg cm^{-2} s^{-1}, 2 - 10 keV), an ultrasoft component was present in the spectrum, and the power law was steeper (α ~3.5 in 1984; in 1983 it was not well-measured); the power spectrum showed a flat-topped band-limited noise component with a break frequency of ~4.5 Hz and a fractional rms amplitude of ~7%. Comparing flux levels, X-ray spectra and power spectra we conclude that in these observations GX 339-4 was in a state intermediate between the usual BHC low and high states. The system was ~4 times brighter than in its usual low state, 4 times fainter than in its usual high state, and an order of magnitude fainter than in its very high state. We compare these results to those recently obtained on other BHCs, and conclude that this ``intermediate state'' behavior is a common characteristic of BHCs, that occurs at $\dot M$ levels intermediate between the high and the low state. We argue that this result can be used to resolve the long-standing issue of the dependence of the power spectral break frequency in the low state on mass accretion rate, and strengthens the idea that low-state noise and very-high state noise may have a common origin. We briefly discuss a possible interpretation for the changes in break frequency in the low state and between low state and intermediate state.